A Role for ChatGPT and AI in Gifted Education. Issue 3 (July 2023) - Siegle, Del
This article explores the potential uses of AI in gifted education programs. Gifted students often have unique learning characteristics and require specialized program services. The use of AI can provide advanced content, personalized learning, creative writing and image manipulation, critical thinking and problem-solving, collaboration, research skills, and advanced technology. ChatGPT and Bing AI can be used to provide additional resources and challenges, design individualized learning plans, provide feedback on writing, and pose challenging questions or problems. While AI has its limitations, it can be a valuable tool for gifted education programs to help meet the needs of gifted and talented students.